Pre and post diagnostic dementia care in four Scottish prisons - Rhoda MacRae; Natalie Chalmers; Debbie Tolson; James Taylor; Kirstin Anderson; Lindsay Thomson; Tom Russ (BMC, 2024)
Abstract Background and purpose The number of older people in prisons is increasing across the globe. Many have poor physical and mental health, higher prevalence of head injury, cognitive impairment and dementia than found in community populations. Meeting the complex needs of this vulnerable group has become an increasing concern for prison and prison healthcare services. The aim of this multi method qualitative study was to investigate how men with diagnosed or suspected dementia were identified, assessed, and cared for in Scottish prisons. It also explored the lived experience of individuals being assessed for or diagnosed with dementia within four prisons. The data from twenty nine interviews was thematically analysed and used to collaboratively propose principles for dementia care in prison and present the resultant co-designed care pathway. Results At the time of data collection almost all the men known to have a dementia diagnosis or suspected dementia had complex health and social care needs, and some were living with advanced dementia. Prison healthcare staff reported taking a 'case by case' approach to their pre- and post-diagnostic care. Meeting these prisoner's needs was complicated by the absence of organisational leads for care of older adults or people with dementia and there was no pathway or model in place to guide staff. Prison healthcare teams often had difficulty accessing specialist community services to support diagnosis. There was a lack of dementia education and knowledge about how to provide pre and post diagnostic dementia care in this setting amongst staff. The findings arising from this research have informed the co-production of two important evidence informed innovations namely a Model of Care and a pre- and post-diagnostic Care Pathway. Conclusion This research adds insights critical to understanding the adequacy of current approaches to meeting dementia related needs within the prison setting. To our knowledge this paper offers the first co-produced evidence informed pre- and post- diagnostic dementia care pathway and model of care for use in prisons. These could serve as tools for change that could enable prison healthcare staff to deliver the right care, at the right time, by the right people, and provide an opportunity to assess risk and plan care for the future.